Dialectics Between Islam and Local Culture in Wetu Telu Lombok Muslims’ Merariq Tradition: An ‘Urf Perspective - Fawaizul Umam; Al Humaidy, Mohammad Ali; Amrulloh, Moh. Asyiq (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2024)
This article discusses dialectical teachings between Islam and local culture among Wetu Telu Muslims, a local community in Lombok, which is often accused of developing a prototype of Islamic teachings mixed with deviant, heterodox, and heretical traditions. The discussion focuses on one form of their traditions that reflects the dialectics, namely the merariq in wedding tradition. By applying a qualitative approach, this study specifically portrayed relevant views of Wetu Telu Muslims which are relatively different from that of orthodox Muslims in Lombok. Based on the results of participatory observation and unstructured in-depth interviews, the study findings reveal that the traditions of the Wetu Telu Muslims, especially in merariq, reflect a dialectical teaching between Islam and local culture so that it can be named as an Islamic tradition. It is also clear that Wetu Telu's teachings are extremely tolerant to the local culture and this is proven, among others, through their wedding tradition. From the ‘Urf perspective, merariq wedding tradition is legitimate for recognition as an Islamic culture or Islamic legal practice even though some aspects of the tradition differ from the general principles of Islamic orthodoxy in Indonesia.